2017
DOI: 10.1136/bjophthalmol-2016-309902
|View full text |Cite
|
Sign up to set email alerts
|

The Malaysian Cataract Surgery Registry: risk Indicators for posterior capsular rupture

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
32
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 16 publications
3
32
1
Order By: Relevance
“…PCR is one of the most significant intraoperative complications of cataract surgery, with a reported incidence of 0.20% to 4.7% . In the present study, the overall rate of anterior vitrectomy for PCR was 0.72% and comparable with those in previous studies.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…PCR is one of the most significant intraoperative complications of cataract surgery, with a reported incidence of 0.20% to 4.7% . In the present study, the overall rate of anterior vitrectomy for PCR was 0.72% and comparable with those in previous studies.…”
Section: Discussionsupporting
confidence: 88%
“…The male sex and preoperative diabetes have been reported as risk factors for intraoperative PCR . Other studies have also reported old age as a risk factor for PCR; however, young patients with a very soft cataract are also at increased risk because the second instrument or phacoemulsification tip can abruptly penetrate the peripheral nucleus and strike or aspirate the capsule . Among socioeconomic variables, residence in a rural area, a lower household income, and surgery in tertiary centres were associated with a higher risk of PCR in our South Korean population.…”
Section: Discussionsupporting
confidence: 46%
See 1 more Smart Citation
“…Intrasurgical complications in our study were rare. e rate of capsular tears was 0.33%, compared with reported rates as low as 0.55% [9], to more commonly reported rates of between 1.14% and 1.78% [10][11][12][13] or occasionally as high as 3.1% [14]. Vitreous loss in our study appeared in 0.33% of cases, compared with reported rates ranging from 0.34% [9] to 2.2% [14]; the incidence of zonular dehiscence (0.40%) and dropped nucleus (0.11%) is also similar or lower compared with that of other reports [10,14].…”
Section: Discussionmentioning
confidence: 78%
“…e rate of capsular tears was 0.33%, compared with reported rates as low as 0.55% [9], to more commonly reported rates of between 1.14% and 1.78% [10][11][12][13] or occasionally as high as 3.1% [14]. Vitreous loss in our study appeared in 0.33% of cases, compared with reported rates ranging from 0.34% [9] to 2.2% [14]; the incidence of zonular dehiscence (0.40%) and dropped nucleus (0.11%) is also similar or lower compared with that of other reports [10,14]. e low rate of intrasurgical complications in our study could be due to several factors: surgery was never performed by ophthalmologists in training and the cases included were operated recently (2017) and outcomes have been reported to improve with time [14][15][16].…”
Section: Discussionmentioning
confidence: 78%